Monocyte heterogeneity and functions in cancer - Olingy, Claire E.; Dinh, Huy Q.; Hedrick, Catherine C. (Journal of leukocyte biology, 2019)
Monocytes are innate immune cells of the mononuclear phagocyte system that have emerged as important regulators of cancer development and progression. Our understanding of monocytes has advanced from viewing these cells as a homogenous population to a heterogeneous system of cells that display diverse responses to different stimuli. During cancer, different monocyte subsets perform functions that contribute to both pro‐ and antitumoral immunity, including phagocytosis, secretion of tumoricidal mediators, promotion of angiogenesis, remodeling of the extracellular matrix, recruitment of lymphocytes, and differentiation into tumor‐associated macrophages and dendritic cells. The ability of cancer to evade immune recognition and clearance requires protumoral signals to outweigh ongoing attempts by the host immune system to prevent tumor growth. This review discusses current understanding of monocyte heterogeneity during homeostasis, highlights monocyte functions in cancer progression, and describes monocyte‐targeted therapeutic strategies for cancer treatment. Review on monocyte heterogeneity, monocyte roles in cancer progression, and therapeutic strategies to target monocytes for cancer treatment.